Memory-impairing effects of local anesthetics in an elevated plus-maze test in mice - Blatt,S.L. (1998)
Post-training intracerebroventricular administration of procaine (20 µg/µl) and dimethocaine (10 or 20 µg/µl), local anesthetics of the ester class, prolonged the latency (s) in the retention test of male and female 3-month-old Swiss albino mice (25-35 g body weight; N = 140) in the elevated plus-maze (mean ± SEM for 10 male mice: control = 41.2 ± 8.1; procaine = 78.5 ± 10.3; 10 µg/µl dimethocaine = 58.7 ± 12.3; 20 µg/µl dimethocaine = 109.6 ± 5.73; for 10 female mice: control = 34.8 ± 5.8; procaine = 55.3 ± 13.4; 10 µg/µl dimethocaine = 59.9 ± 12.3 and 20 µg/µl dimethocaine = 61.3 ± 11.1). However, lidocaine (10 or 20 µg/µl), an amide class type of local anesthetic, failed to influence this parameter. Local anesthetics at the dose range used did not affect the motor coordination of mice exposed to the rota-rod test. These results suggest that procaine and dimethocaine impair some memory process(es) in the plus-maze test. These findings are interpreted in terms of non-anesthetic mechanisms of action of these drugs on memory impairment and also confirm the validity of the elevated plus-maze for the evaluation of drugs affecting learning and memory in mice